A self-delivery photodynamic sensitizer for enhanced DNA damage by PARP inhibition. (17th November 2022) - Kong, Ren-Jiang; Li, Xin-Yu; Huang, Jia-Qi; Zhou, Xiang; Deng, Fu-An; Li, Yan-Mei; Liu, Ling-Shan; Li, Shi-Ying; Cheng, Hong
Abstract : Self-delivery photodynamic sensitizer is developed via the self-assembly of a photosensitizer and an inhibitor of Poly(ADP-ribose) polymerase (PARP), which enhances oxidative damage in tumor by blocking DNA repair pathway through PARP inhibition. Abstract : Tumor cells activate DNA repair pathways to combat the oxidative damage induced by reactive oxygen species (ROS), contributing to their resistance to photodynamic therapy (PDT). Herein, a self-delivery photodynamic sensitizer is developed to enhance oxidative damage by blocking the DNA repair pathway through poly(ADP-ribose) polymerase (PARP) inhibition. Specifically, the photodynamic sensitizer (CeOla) is constructed based on the self-assembly of the photosensitizer chlorine e6 (Ce6) and the PARP inhibitor olaparib (Ola). Of note is that carrier free CeOla has a high drug content and favorable water stability, which could be effectively internalized by tumor cells for robust PDT upon light irradiation. Moreover, CeOla could inhibit the activation of PARP, promote the upregulation of γ-H2AX and reduce the expression of Rad51, thereby blocking the DNA repair pathway to sensitize tumor cells for PDT. As a consequence, the self-delivery CeOla greatly promotes the tumor cell apoptosis and shows a high antitumor performance with low side effects. It serves as a novel platform for the development of self-delivery nanomedicine to overcome oxidative resistance in tumor treatment.